2021
DOI: 10.1037/drm0000180
|View full text |Cite
|
Sign up to set email alerts
|

Are we dreaming or are we awake? A quali–quantitative analysis of dream narratives and dreaming process during the COVID-19 pandemic.

Abstract: The COVID-19 pandemic and the restrictive measures taken against the spread of the contagion can be considered as traumatic events having a major impact on mental health. Dreams after undergoing traumatic experiences could "replay" traumatic scenes or have a para-therapeutic role that facilitates connections between a traumatic event and associated emotions. However, the studies carried out thus far in the field of sleep and dreams during the COVID-19 pandemic have mostly focused on sleep disorders, emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 73 publications
3
24
0
Order By: Relevance
“…Positive dream emotions were predicted by the presence in dreams of open places or places of escape, relationality that unites, and positive processes, while working in health care predicted a higher frequency of unborn person in dreams. The same research group ( Margherita et al, 2021 ) analysed the narratives of the most recent dream during the lockdown period using T-Lab ( Lancia, 2004 , 2008), a quali-quantitative software for text analysis that identifies meaning dimensions and themes on the basis of the comparison of different lexical profiles. The authors found 4 thematic clusters: escape from the threat, the work of mourning, unrecalled dreams, COVID-19 as manifest content.…”
Section: Resultsmentioning
confidence: 99%
“…Positive dream emotions were predicted by the presence in dreams of open places or places of escape, relationality that unites, and positive processes, while working in health care predicted a higher frequency of unborn person in dreams. The same research group ( Margherita et al, 2021 ) analysed the narratives of the most recent dream during the lockdown period using T-Lab ( Lancia, 2004 , 2008), a quali-quantitative software for text analysis that identifies meaning dimensions and themes on the basis of the comparison of different lexical profiles. The authors found 4 thematic clusters: escape from the threat, the work of mourning, unrecalled dreams, COVID-19 as manifest content.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, it is emphasized that the loss and grief experienced directly due to COVID-19 are directly related to pandemic dreams (Barrett, 2020; Schredl & Bulkeley, 2020). Moreover, it was stated that individuals experiencing losses brings their ego together with the real or imaginary sense of loss of the individuals they lose, providing psychic balance through representations of the past placed in the unconscious memory (Margherita et al, 2021). In addition to the dreams of death and mourning, the content of the dreams of the participants was characterized by chaotic situations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the theme linked with the lack of dream recall might be interpreted as a way to shrink the contact with psychic and emotional reality, representing both a functional and dysfunctional defense mechanism during the COVID-19 pandemic. Indeed, the lack of dream recall permits keeping some traumatic elements out of consciousness, to preserve sleeping as well as potentially being a way to avoid the fatigue of elaborate intense emotions (Margherita et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully, the present study contributes to considering dreaming processes as indexes of health of individuals, confirmed by the literature which highlights the importance to explore the effects of the pandemic, through the dreamingwaking continuum, on clinical and nonclinical population, aimed at identifying possible longterm distress risks (Caffieri & Margherita, 2021;Margherita et al, 2021;Prati & Mancini, 2021). Consequently, our findings suggest that clinicians may assess the role of dreaming in MDers to better direct clinical interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation